1988
DOI: 10.1051/gse:19880201
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a quantitative character radius incompletus, temperature effects, and localization of a mobile genetic element Dm-412 in Drosophila melanogaster

Abstract: SummaryThe radius incompletus mutation (ri) causes a gap in the radial wing vein, L2. A control line (riC) of the mutation ri was selected for increase and decrease of radial vein. In the riSN strain, extreme expression of this quantitative character is almost complete elimination of L2 (negative selection : SN). In the riSP strain, the L2 vein is almost restored (positive selection : SP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This suggested that passage to cell culture could trigger transposition, and reoriented the interest in cultured cells as an experimental system for the study of induction of transposition. The background for this interest is the body of facts and speculations on the ability of various environmental stresses to induce transposition or putative intermediates of transposition in plants and plant cultured cells (McClintock, 1984;Doting & Starlinger, 1986;Cullis, 1990), yeast (Paquin & Williamson, 1988;Rolfe et aL, 1986), mammals (Weinstein et al, 1988) and Drosophila Vasilyeva et al, 1988;Strand & McDonald, 1985;McDonald et al, 1988;Georgiev et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…This suggested that passage to cell culture could trigger transposition, and reoriented the interest in cultured cells as an experimental system for the study of induction of transposition. The background for this interest is the body of facts and speculations on the ability of various environmental stresses to induce transposition or putative intermediates of transposition in plants and plant cultured cells (McClintock, 1984;Doting & Starlinger, 1986;Cullis, 1990), yeast (Paquin & Williamson, 1988;Rolfe et aL, 1986), mammals (Weinstein et al, 1988) and Drosophila Vasilyeva et al, 1988;Strand & McDonald, 1985;McDonald et al, 1988;Georgiev et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). In the experiments with HS of line N 49, there were 13 different positions, and only 6 positions among them coincided with transposition sites induced by the stepwise temperature treatment of the ric population temperature lines ric113 and ric149 (2,3). Perhaps these differences reflect the properties of different treatments.…”
mentioning
confidence: 99%
“…respectively, 3.4 x 10-2, 8.7 x 10-2, and <4.1 x 10-4 transpositions per genome per occupied position per generation. Therefore, as a result of heat shock treatment, the probabilities of transpositions were two orders of magnitude greater than those of the control sample in the next generation after induction.…”
mentioning
confidence: 99%
See 2 more Smart Citations